Implementing predictive tools in surgery: A narrative review in the context of orthopaedic surgery. Issue 12 (15th September 2022) - Zhou, Yuxuan; Gould, Daniel; Choong, Peter; Dowsey, Michelle; Schilling, Chris
Abstract: Clinical predictive tools are a topic gaining interest. Many tools are developed each year to predict various outcomes in medicine and surgery. However, the proportion of predictive tools that are implemented in clinical practice is small in comparison to the total number of tools developed. This narrative review presents key principles to guide the translation of predictive tools from academic bodies of work into useful tools that complement clinical practice. Our review identified the following principles: (1) identifying a clinical gap, (2) selecting a target user or population, (3) optimizing predictive tool performance, (4) externally validating predictive tools, (5) marketing and disseminating the tool, (6) navigating the challenges of integrating a tool into existing healthcare systems, and (7) developing an ongoing monitoring and evaluation strategy. Although the review focuses on examples in orthopaedic surgery, the principles can be applied to other disciplines in medicine and surgery. Abstract : Clinical predictive tools are a topic gaining interest. Of all predictive tools developed, only a small proportion are implemented into clinical practice. In this narrative review, we discuss the key principles that guide the translation of predictive tools into clinical practice. We focus on examples in orthopaedic surgery. However, the principles discussed can be applied to other aspects of medicine and surgery.